Pazopanib in Pulmonary Epithelioid Hemangioendothelioma: Report of a Case - Ahalli, Ibtihal; Oualla, Karima; Hejjane, Loubna; Boujarnija, Raihana; Messoudi, Kaouthar; Mai, Adil; Reggad, Fatima Zahrae Er; Amaadour, Lamiaa; Benbrahim, Zineb; Arifi, Samia; Alami, Badr; Chbani, Laila; et al. (International Journal of Innovative Research in Medical Science, 2020)
Pulmonary epithelioid hemangioendothelioma (PEH) is a rare vascular tumor of borderline or low-grade malignancy, Vascular endothelial growth factor (VEGF) and the VEGF receptor were found on PEH tumor cells, suggesting that target therapies that block VEGFR have a logical base in this rare malignancy. We report a 25 years old woman with a pulmonary hemangioendothelioma, treated with pazopanib, the only anti angiogenic registered agent for sarcoma, with clinical improvement of symptoms and durable stabilization for more than two years of lung tumor.